Staff Commitment to Providing Tobacco Dependence in Drug Treatment: Reliability, Validity, and Results Of a National Survey - Hunt, Jamie J. (2013)
Although most people in treatment for illicit drug use smoke cigarettes, few facilities offer any form of treatment for tobacco dependence. One reason for this may be that drug treatment staff have varying levels of commitment to treat tobacco. We developed and validated a 14-item Tobacco Treatment Commitment Scale (TTCS), using 405 participants in leadership positions in drug treatment facilities. We first conducted a confirmatory factor analysis to evaluate four a priori domains suggested by our original set of 38 items—this did not produce a good fit (CFI=0.782, RMSEA=0.067). We then conducted a series of exploratory factor analyses to produce a more precise and reliable scale. The final confirmatory factor analysis indicated a three-factor solution, produced a good fit (CFI=0.950, RMSEA=0.058), and had substantial unified reliability of 0.975. The final TTCS contained 14 items in 3 domains: Tobacco is less harmful than other drugs; It’s not our job to treat tobacco; and Tobacco treatment will harm clients. These constructs account for most of the variance in the survey items and emerged as major sentiments driving staff commitment to providing tobacco services. The TTCS can be used to understand the role of staff attitudes in the adoption of tobacco services in this important treatment setting.